Factors affecting the increasing of online identity theft : a study in Kota Bharu Kelantan / Noor Ain Mohd Ariffin - Mohd Ariffin, Noor Ain (2012)
The aim of this study was to examine the “Factor Affecting The Increasing Of Online Identity Theft, A Study In Kota Bharu”. There are three (4) independent variables that been studied, which were Consumer Behaviour, Education, Government react and Security Tools. Moreover, questionnaire had been used in order to get feedback from employees. Researcher had distributed 200 questionnaires around Kota Bharu. The sampling used is non probability, convenience sampling. The data collected was then tested on its frequency and reliability analysis. Simple regression analysis, t-test analysis and were used to test the hypothesis in this study. The finding on reliability was excellent and it considers that all dependent are acceptable. The findings of this paper suggest three factors are significant factors for factors that affect the increasing of online identity theft are, consumer behaviour, education and government react. Based from the results obtained in this study, researcher suggests some recommendations like provide more awareness to the public on the importance of keeping the personal information only to yourself. Furthermore, the financial institution should up to date with the security improvement from time to time because hackers also will always improve their skills from time to time